(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Rasashastra is the Iatrochemistry of Ayurveda which deals with formulations containing herbals, minerals and metals. Various Kalpanas are mentioned in Rasashastra such as Pottali Kalpana, Kharaliya Kalpana, Parpati Kalpana. Dravaka Kalpana is one among them which is made out of predominately “Lavana- Kshara” Dravyas. Dravaka Kalpana is a liquid dosage form that is prepared either by using Agni or without the use of Agni. Shankha Dravaka is one such Dravaka Kalpana that is mentioned in the different classical texts. It is indicated in various diseases such as Gulma (abdominal lump), Shoola (pain), Yakrit Dosha (disorders of the Liver), Pliha (splenic disorders), Ashmari (calculus) etc. It is used in less dosage by diluting with water. Different Acharyas have mentioned different methods of its preparation. This article compiles review of Ayurvedic literature on Shankha Dravaka. This literature review is carried out to create the base for undertaking future research work because without research efficacy, the utility cannot be established